To Assess the Study of Pro- BNP, CPK -MB and Troponin Level in Acute Myocardial Infarction - Ranjit Ambad; Dattu Hawale; Pradip Jain (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: One of the greatest causes of death and morbidity in the world is acute myocardial infarction(AMI). Atherosclerotic coronary artery disease (CAD) with plaque erosion or breakup, causing transient,partial or total arterial occlusion, is the most common cause of AMI. Without appropriate blood flow, theheart cannot continue to function, and if it is severely compromised, death is inevitable. Simple and objectivemeasures of cardiac function are brain natriuretic peptide (BNP) levels. These measurements can be used todiagnose heart failure, including diastolic dysfunction, and have been shown to save money by using themin the emergency room setting. For the diagnosis of acute myocardial infarction, the most sensitive and mostprecise measure available is creatine phosphokinase (CPK-MB). The main biomarker for AMI diagnosis iscardiac troponin I. The level of troponin may also be elevated with important prognostic value in many otherdisorders, including heart failure.Methods: This study was a case-control study, conducted in the Medicine and cardiology Department atDMMC & SMHRC, Nagpur in collaboration with ABVRH, Sawangi (Meghe) during Nov 2020 to Jan 2020.Total 80 individuals were considered for the study, 40 each in case and 40 in control groups.Results: As present study show the Pro-BNP Levels were increased significantly (P<0.001) in the AMI(2200±601.30) as compared in controls (90.20±3.20). The mean values of serum CK-MB and troponin Iwere significantly (P<0.001) higher in the AMI (165±47.21, 1.48±0.45) as compared to those in the healthycontrols (11.50±0.80± 3.250, 0.03±0.01) respectively.Conclusions: These findings therefore indicate that the combined detection of CK-MB, Troponin I and NTPro-BNP levels will contribute significantly to the early diagnosis of AMI. It can also provide the clinic withdiagnostic evidence and thus reduce AMI mortality in the acute phase.